Philippine government budgeting : policy and practice in the new society - Laya, Jaime C. (Manila : Ministry of the Budget, 1980)
This principle contrasts with that in less impatient governments, where legislation tends to sanctify long standing practice and tradition.
Chapter 1. Introduction -- Chapter 2. Budget policy and magnitudes -- Chapter 3. Budget preparation and legislation -- Chapter 4. Budget execution -- Chapter 5. Budget accountability and mechanics -- Chapter 6. Revenue and debt management -- Chapter 7. Organization, staffing and compensation -- Chapter 8. Budgeting in local governments and government -- Chapter 9. Conclusion.
Keywords: GOVERNEMENT - BUDGETING